WTO membership and its critical importance to China. - Wong, Chak Mun. (2008)
For the political regime in China, WTO membership is crucial to the realisation of its vision for 21st Century China. This vision involves the resolution of three important issues. The first is the survival of the political regime by maintaining internal stabililty and preventing chaos, through policies which would yield high growth rates and improve standards of living. Additionally, it has to be seen as preserving China's sovereignty and position in the world. The second relates to the development of its national economic strength so that China could maintain its status as a major power. To do this China has to remain internationally competitive which requires it to integrate into the global economy via a open market economy. The third deals with China's technological backwardness, especially that of its military, and how it could be overcomed, as it has not only a direct impact on the economic development of China, but also to the preservation of China's unity, sovereignty and territorial integrity. The current political leadership has decided to develop a market economy fully integrated to the global economy as the only way to resolve the three issues. Opening up China completely to the world for the required investments, technology and markets has become neccessary for achieving its long term development goals and for completing its modernisation process. Joining the WTO has thus become a strategic objective.